Climate change effects and human pressure in coastal areas of naturalistic value: a multi-technique approach applied to Cala del Cefalo (Southern Italy) - Alessia Sorrentino; Giovanni Fasciglione; Claudia Caporizzo; Diana Di Luccio; Aniello Florio; Gaia Mattei; Maria Francesca Tursi; Pietro P.C. Aucelli (Quaternary International, 2026)

Lightly reinforced concrete walls in formwork blocks for the combined seismic and energy retrofit of masonry structures - Silvia Caprili; Giuseppe Chellini; Francesca Mattei; Walter Salvatore; Gemma Simonetti; Massimo Badalassi (Engineering Structures, 2024)

Corrosion effects on the dissipative performance of critical regions of RC frame systems - Silvia Caprili; Francesca Mattei; Walter Salvatore (Engineering Structures, 2024)

Thermal transient PDC behavior induced by topographic drops: A test case at Mt. St. Helens, USA - Matteo Trolese; Matteo Cerminara; Guido Giordano; Brittany D. Brand; Nicholas Pollock; Francesca Cifelli; Massimo Mattei (Earth and Planetary Science Letters, 2024)

Analogies and Differences Between Dental Stem Cells: Focus on Secretome in Combination with Scaffolds in Neurological Disorders - Francesca Santilli; Jessica Fabrizi; Costantino Santacroce; Daniela Caissutti; Zaira Spinello; Niccolò Candelise; Loreto Lancia; Fanny Pulcini; Simona Delle Monache; Vincenzo Mattei (Stem Cell Reviews and Reports, 2024)
Mesenchymal stem cells (MSCs) are well known for their beneficial effects, differentiation capacity and regenerative potential. Dental-derived MSCs (DSCs) are more easily accessible and have a non-invasive isolation method rather than MSCs isolated from other sources (umbilical cord, bone marrow, and adipose tissue). In addition, DSCs appear to have a relevant neuro-regenerative potential due to their neural crest origin. However, it is now known that the beneficial effects of MSCs depend, at least in part, on their secretome, referring to all the bioactive molecules (neurotrophic factors) released in the conditioned medium (CM) or in the extracellular vesicles (EVs) in particular exosomes (Exos). In this review, we described the similarities and differences between various DSCs. Our focus was on the secretome of DSCs and their applications in cell therapy for neurological disorders. For neuro-regenerative purposes, the secretome of different DSCs has been tested. Among these, the secretome of dental pulp stem cells and stem cells from human exfoliated deciduous teeth have been the most widely studied. Both CM and Exos obtained from DSCs have been shown to promote neurite outgrowth and neuroprotective effects as well as their combination with scaffold materials (to improve their functional integration in the tissue). For these reasons, the secretome obtained from DSCs in combination with scaffold materials may represent a promising tissue engineering approach for neuroprotective and neuro-regenerative treatments. Graphical Abstract

The simultaneous stable isotope analysis of skin and blood gives insights on habitats shifts in Mediterranean loggerhead turtles (Caretta caretta, Linneus 1758) - Michelle Gelippi; Monica Francesca Blasi; Marco Friedrich Walter Gauger; Gabriele Favero; Daniela Mattei; Sandra Hochscheid; Andrea Camedda; Giuseppe Andrea de Lucia; Davide Cicala (Estuarine, Coastal and Shelf Science, 2023)

Regenerative Potential of DPSCs and Revascularization: Direct, Paracrine or Autocrine Effect? - Vincenzo Mattei; Stefano Martellucci; Fanny Pulcini; Francesca Santilli; Maurizio Sorice; Simona Delle Monache (Stem Cell Reviews and Reports, 2021)
A new source of mesenchymal stem cells has recently been discovered, the so-called dental pulp derived stem cells (DPSCs) which therefore could represent potentially tools for regenerative medicine. DPSC originate from the neural crest and are physiologically involved in dentin homeostasis; moreover, they contribute to bone remodeling and differentiation into several tissues including cartilage, bone, adipose and nervous tissues. DPSCs have also been shown to influence the angiogenesis process, for example through the release of secretory factors or by differentiating into vascular and/or perivascular cells. Angiogenesis, that has a pivotal role in tissue regeneration and repair, is defined as the formation of new vessels from preexisting vessels and is mediated by mutual and reciprocal interactions between endothelial cells and perivascular cells. It is also known that co-cultures of perivascular and endothelial cells (ECs) can form a vascular network in vitro and also in vivo. Since DPSCs seem to have characteristics similar to pericytes, understanding the possible mechanism of interaction between DPSCs and ECs during neo-angiogenesis is dramatically important for the development of advanced clinical application in the field of regeneration. Graphical abstract

Experimental analysis on cyclic performance of concrete columns with TempCore or Dual-Phase steel reinforcement - Silvia Caprili; Giuseppe Chellini; Francesca Mattei; Federico Romis; Walter Salvatore (Bulletin of Earthquake Engineering, 2020)

Vibration Testing Procedures for Bone Stiffness Assessment in Fractures Treated with External Fixation - Lorenza Mattei; Antonia Longo; Francesca Di Puccio; Enrico Ciulli; Stefano Marchetti (Annals of Biomedical Engineering, 2017)

A multidisciplinary approach to the study of the Montereale Basin (Central Apennines, Italy) - Edi Chiarini; Elena La Posta; Francesca Cifelli; Chiara D’Ambrogi; Valeria Eulilli; Fernando Ferri; Maurizio Marino; Massimo Mattei; Luca Maria Puzzilli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

Familiarity of Physicians, Translational Researchers, Nurses, and Other Health Professionals with Evidence-Based Medicine Terms and Resources - Donatella Ugolini; Georgia Casanova; Marcello Ceppi; Francesca Mattei; Monica Neri (Journal of Cancer Education, 2014)

The emplacement of the Late Miocene Monte Capanne intrusion (Elba Island, Central Italy): constraints from magnetic fabric analyses - Francesca Cifelli; Liliana Minelli; Federico Rossetti; Giorgia Urru; Massimo Mattei (International Journal of Earth Sciences, 2012)